Kajian Psikolinguistik Pada Proposisi Citra Merek - Fauziah, Anisatul (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
This study aims to examine or analyze the proposition on the brand image of noodles and meatballs in lumajang based on psycholinguistic review. Research on language proposition on brand image using qualitative research type and designed using case study design. The relationship between the arguments and predictions that emerged in the research data showed varied languages. The contents of the proposition on the brand image of "bakso beranak", "mie nyonyor" and demon noodles show a logical and detailed relationship between each argument and predication. The content of the brand image proposition "baksojudes" does not indicate the relation of argument and predication. The interproposition relationship of "bakso beranak" shows the description of the presentation. The interproposition relationship of "bakso judes", "mie nyonyor", and "mie iblis" shows descriptions of taste. The uniqueness of the proposition's contents on the "meatballs beranak" shows the description of the packaging and form of presentation. The uniqueness of the proposition's content on "bakso judes", "mie nyonyor ", and "mie iblis" shows a flavor description, so that the brand can attract consumers.